A model for habitus-adjusted paediatric weight estimation by age and data concerning the validation of this method on a large dataset of English children. - Appelbaum,N; Clarke,J; Maconochie,I; Darzi,A (Data in Brief, 2017)
It is often not possible to weigh children upon arrival at an emergency room before commencing the provision of emergency care. Because drugs for children are prescribed on the basis of age and body weight, estimations of weight are necessitated. Age-based equations have been one of the most commonly used weight estimation strategies historically. Due to the variability of weight for age in children, and variations in body habitus, these methods are inaccurate by design (Young and Korotzer, 2016) [1].